Exploring the value relevance of biological assets and bearer plants: An analysis with IAS 41 Revision - Bispo, T. (2022)
The purpose of this paper is to explore whether a relation exists between share market valuation and the accounting information about bearer plants and biological assets. The focus is supported in the most recent revision of IAS 41 Agriculture. This revision formally introduced the concept of bearer plants, moved them from biological assets to PP&E, and changed their prior measurement by the fair value model to the cost model. Our approach explores the usefulness of these changes under a valuation market approach. Our analysis settles that there is a positive association between share prices and agricultural-related assets. Overall, our results suggest that biological assets are value relevant and reveal that bearer plants are incrementally value relevant after IAS 41 revision. Besides, we envisage that these conclusions are driven by companies in countries where the value add of agriculture, forestry, and fishing as a percentage of the country’s GDP is lower.